Comparison of Left Ventricular Function after His Bundle Pacing vs Left Bundle Branch Area Pacing Implantation - Prakoso, Kurniawan; Wibawa, Kevin; Karwiky, Giky; Akbar, Mohammad Rizki; Martha, Januar Wibawa; Iqbal, Mohammad (The Indonesian Heart Association, 2024)
Background: Right ventricular pacing may lead to deterioration of left ventricular (LV) function. Recent guideline suggests the use of conduction system pacing (CSP) with either his bundle pacing (HBP) or left bundle branch area pacing (LBBAP). This study aimed to investigate the difference of LV function between HBP and LBBAP. Methods: This is a prospective cohort study enrolling patients age >18 years requiring CSP implantation from June 2020 to January 2024 in Hasan Sadikin General Hospital, Bandung. Data regarding QRS duration and several echocardiography parameters were obtained at baseline and during follow up within 1 year after CSP implantation. Results: From 66 patients, 35 were included in the HBP group. There was no difference in QRS duration at baseline between both groups with higher left ventricular ejection fraction (LVEF) in HBP group (51.2 ± 13.9% vs 45.6 ± 11.1%, p=0.078). During follow up, HBP group showed narrower QRS duration (113.40 ± 17.06ms vs 120.81 ± 12.12ms, p=0.029). LV function was preserved in HBP group while there was a trend of LV function improvement in LBBAP group (53.1 ± 11.7% in LBBAP vs 53.9 ± 11.5% in HBP group, p=0.536). Further analysis in 33 patients with LV dysfunction showed a trend of LVEF improvement in both groups (35.3 ± 7.9% to 44.6 ± 11.28% in HBP and 38.7 ± 6.9% to 51.4 ± 13.1% in LBBAP group). Conclusion: HBP resulted in narrower QRS complex. However, both HBP and LBBAP showed a trend of LV function improvement in patients with LV dysfunction.